Analisis Keselamatan Kerja Pada Sistem Pengoperasian Forklift Dan Crane Guna Mencegah Kecelakaan Kerja - Meysa Atika Puteri; Harianto Harianto; Threevaldo Joan Saputra; Musdalifah Akbar Simanjuntak; Edwin Randalangi; Athira Salsabila; Andi Hamril Vikri Al Farisi (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
The propeller is a key component in ship propulsion as a means of producing thrust to move the ship. The damage that At any time in the work process there is always the possibility of work accidents. Forklifts and cranes are lifting and transport aircraft that support the implementation of the production process or work with a fairly high potential for danger. In this study, we will discuss in more depth what forklifts and cranes are, what are their advantages and disadvantages, what are their uses, and what important components are found in forklifts and cranes. Therefore, there is a need for an analysis of the use of lifting equipment to be used in order to produce the right alternative lifting equipment in carrying out a job. This research was conducted using a descriptive method that provides an overview of the application of work safety regulations in the operation of forklifts and/or cranes. The results of this study will then be evaluated so that an improvement can be determined so that the operation of forklifts and cranes can be safe. This research was conducted using a descriptive method that provides an overview of the application of work safety regulations in the operation of forklifts and/or cranes. The results of this study will then be evaluated so that an improvement can be determined so that the operation of forklifts and cranes can be safe.